Development of micro-calorimeter system to characterize thermal behavior of biofilm - Huynh, Alain Phuoc Tho (2018)
Environmental biofilms and human microbiomes are complexed microbial communities. No only the structure, but also the dynamics of the social interactions and the physico-chemical properties of biofilms are highly dependent on local environmental stresses, such as pH, nutrient availability or temperature. Studying of the effect of temperature on microbial biofilms has been mainly limited by the lack of high-precision experimental tools, capable of regenerating complex, well-controlled and reproducible micro-environmental conditions where temperature is the only variable parameter. The objectives of this work was to design, develop, and validate experimental platforms with the potential to (a) reproduce complex but well defined micro-environmental gradients relevant for microbial biofilms (flow velocity, nutrient, temperature), and (b) monitor dynamics of biofilm (development, dispersal, death) using temperature as readout signal. In order to demonstrate the potential for applications of these newly developed experimental set-ups, proof of concept studies were performed. Using Pseudomonas aeruginosa and Pseudomonas putida as medical and environmental model organisms for biofilms, proof of concept studies included (a) study of early stages of biofilm development at high spatial and temporal resolution under well-defined micro-environmental gradients, (b) assessment of the effect of temperature on biofilm formation using a temperature gradient, and (c) use of biofilm thermal signature to characterise major biofilm behaviour (biofilm formation or dispersal). Three devices were designed, micro-fabricated and validated: a new microfluidic flow through chamber allowing for multidirectional flow conditions as well as spatial and temporal characterisation; a sensitive temperature controlled system to be combined with the flow chamber in order to generate well-defined temperature gradients; a 3D thermopile for high precision temperature sensing. Using these sophisticated devices, we provided preliminary evidences that the initial stage of biofilm formation is a complex phenomenon, highly dependent on the bacterial communities and the local micro-environmental gradients. P. aeruginosa and P. putida demonstrated strain specific behaviors within the first 12 hours of biofilm formation (initial attachment, clonal development, first dispersal, and reattachment). These behaviors were also found to be highly dependent on the flow velocity, which indirectly drives nutrient and oxygen availability, and temperature, which impacts on cellular activity and physical characteristics of the local environment. These preliminary results support the need for further research to assess in real time the impact of temperature on social microbial interactions within biofilms, using high precision, complex and well-controlled environmental conditions. Finally, biofilm behaviors (build up, dispersal and eradication) were assessed using temperature as readout parameter using a sensitive thermal sensor combined with the new microfluidic flow chamber. A good correlation between heat signal and biovolume measurements was observed, suggesting the potential of this experimental approach for further applications, such as drug screening. In conclusion, biofilm development depends on physical and chemical micro-environmental gradients surrounding the local biofilm clusters. Flux measurements are therefore warranted to observe the heterogeneity of biofilms, and the newly developed devices offer users unique experimental conditions to study biofilm behaviors at high spatial and temporal resolutions.